If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 8(2m + 1) = 11116m Reorder the terms: 3 + 8(1 + 2m) = 11116m 3 + (1 * 8 + 2m * 8) = 11116m 3 + (8 + 16m) = 11116m Combine like terms: 3 + 8 = 11 11 + 16m = 11116m Solving 11 + 16m = 11116m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-11116m' to each side of the equation. 11 + 16m + -11116m = 11116m + -11116m Combine like terms: 16m + -11116m = -11100m 11 + -11100m = 11116m + -11116m Combine like terms: 11116m + -11116m = 0 11 + -11100m = 0 Add '-11' to each side of the equation. 11 + -11 + -11100m = 0 + -11 Combine like terms: 11 + -11 = 0 0 + -11100m = 0 + -11 -11100m = 0 + -11 Combine like terms: 0 + -11 = -11 -11100m = -11 Divide each side by '-11100'. m = 0.000990990991 Simplifying m = 0.000990990991
| 3c-7+c=2c-14 | | 3(4y-2)=3y-24 | | 2(x-5)=3(20-x) | | 4b-3=0 | | 5aw^2-36b+bw^2-180a= | | -4s=-4s-7 | | 39=3y-15 | | 10/x=5/7 | | 4-8y= | | -12x+y+7-(-x)+9y+(-7)= | | x^2-17x-7= | | 2x+24=10x+16 | | 46=6+1y | | 1.6+m=2.5 | | 6ax-9a+10x-15= | | 1=.4x-.8x-35 | | -j-10=-j | | 8-U=3 | | 6x+17=8x-1 | | -10d-10=-10d | | -60x^3+27x^2-3x= | | X^5/6-x^1/6 | | 3x+5+6x-2=4x-7 | | 6n=1.5n | | 8x/5-3=29 | | 1+1a=2 | | 4x+7+y=22 | | 25a^2-49= | | x^2+11x=36 | | 6y-5x=12fory | | 3(x+1)=8(x-2)+6 | | 36x^3+3x^2-18x= |